#USvsHate: the power and core tensions of using an 'anti-hate' onramp for K12 antiracism today. Issue 4 (7th June 2022) - Pollock, Mica; Yoshisato, Mariko
ABSTRACT: This paper launches public analysis of #USvsHate ('us versus hate'), a collective initiative to invite 'anti-hate' lessons and youth-made public messaging in U.S. schools. Building on multiple research traditions, the Authors designed and piloted #USvsHate regionally, then nationally, starting in 2017. Here, we explore the pros and cons of using an 'anti-hate' frame as an onramp to K12 work against bias, injustice, and racism particularly, in an era of emboldened bigotry. As antiracist project designers, we had specific hopes and worries regarding the 'anti-hate' onramp, particularly the worry that its focus on heightened cruelty might turn students' attention away from normalized bias and structural inequality. This paper tracks our initial effort to leverage a frame avoided by scholars, given its K12 utility and familiarity.